Hubungan Psychological Well Being dengan Hipertensi Pada Lansia Penderita Hipertensi di Wilayah Kerja Puskesmas Gugak Panjang - Izzati, Wisnatul; Damaiyanti, Siska; Irwan, Ersha Meita (Universitas Pahlawan Tuanku Tambusai, 2024)
Hypertension is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg. One of the factors causing hypertension can be a person's psychological condition. Psychological problems such as stress and unstable emotions. Stress and unstable emotional states can have an effect on high blood pressure because they affect the immune system. Psychological well being is the state of a person who has positive behavior towards himself and others, is able to control the environment, and has a goal in life. A preliminary study carried out at the Guguak Panjang Community Health Center found that the number of elderly people suffering from hypertension was 172 people. The aim of the research is to find out